The importance of climate scenarios in setting the productivity indexes in the pampa arenosa sub - region of the Province of Buenos Aires, Argentina - Pérez, Silvia Patricia (2019)
Fil: Pérez, Silvia Patricia. Universidad de Buenos Aires. Facultad de Agronomía. Departamento de Recursos Naturales y Ambiente. Buenos Aires, Argentina.